What hinders team innovation performance? Three-way interaction of destructive leadership, intra-team conflict, and organizational diversity - Choi, Suk Bong; Jung, Ki Baek; Kang, Seung-Wan (Frontiers in Psychology, 2022)
This paper aims to clarify the impact of destructive leadership on team innovation performance. It also explores the relevant conditions that maximize the above relationship. Specifically, we examine how intra-team conflict and organizational diversity moderate the relationship between destructive leadership and team innovation performance. Finally, the three-way interaction between destructive leadership, intra-team conflict, and organizational diversity is analyzed for the worst conditions to maximize the negative effect of destructive leadership on team innovation performance. This paper used a cross-sectional design, with questionnaires administered to 87 teams with 479 team members working in Korean manufacturing and service firms. It applied a hierarchical regression analysis to test the hypothesized relationships including three-way interaction effect among destructive leadership, intra-team conflict, and organizational diversity on team innovation performance. This paper provided empirical insights about how destructive behaviors of team leader hindered team innovation performance. The three-way interaction effects also revealed that the higher the levels of both intra-team conflict and organizational diversity, the greater the negative effect of destructive leadership on team innovation performance. This paper demonstrates how team leaders’ behavior and team and organizational conditions result in discouraging overall innovation outcomes. This paper contributes to the innovation and leadership literatures by identifying possible leadership type hindering innovation performance at team level, and the specific conditions and their dynamic interaction strengthening the negative effect of destructive leadership on team innovation performance.